Recovery of muscle strength and power after limb-lengthening surgery. - Barker, K; Lamb, S; Simpson, H (2010)
OBJECTIVE: To report muscle strength, power, and function after limb-lengthening surgery performed by using the Ilizarov technique. DESIGN: Prospective, longitudinal observational study of a cohort of consecutive patients who underwent limb-lengthening distraction followed up for 2 years after surgery. SETTING: National Health Service hospital specializing in orthopedic surgery. PARTICIPANTS: Patients (N=16) who had undergone limb-lengthening surgery performed by using the Ilizarov method (11 men, 5 women; mean age=27 y; range, 13-56 y). INTERVENTIONS: None. MAIN OUTCOME MEASURES: Muscle strength and power were assessed by using 2 validated measures: isokinetic concentric strength of the quadriceps and hamstrings measured by using a dynamometer and leg extensor power. Measures were recorded preoperatively and at 6, 12, and 24 months after the completion of lengthening. Function was measured by 2 timed tests of functional performance: stair climbing and sit-to-stand. RESULTS: Overall results were good with high reports of function and satisfactory clinical examination. Both concentric muscle strength and leg power showed a clear pattern of decreased muscle strength at 6 months after frame removal, improving throughout the study period until it was within 3% of the preoperative value at 2 years. By 2 years, self-reported function and ability to complete timed functional tests had returned to or improved on the preoperative values. Muscle strength remained slightly below the preoperative value; this was more pronounced in the quadriceps than the hamstrings. There was no association between muscle strength and the amount of lengthening that had been undertaken. CONCLUSIONS: This study suggests that there is a small residual decrease in muscle strength and power after limb-lengthening surgery but that these do not adversely impact on a patients' ability to perform everyday functional activities.